Extensive tailoring of REPO4 and REVO4 crystallites via solution processing and luminescence. Issue 27 (23rd June 2022) - Li, Meiting; Li, Ji-Guang
Abstract : This article highlighted the recent achievements in crystal engineering of REPO4 and REVO4 via solution processing, with an emphasis on solution chemistry, the role of chelate ion, crystallization mechanism and luminescence properties. Abstract : Rare-earth orthophosphate (REPO4 ; RE = La–Lu lanthanide, Y) and orthovanadate (REVO4 ) are attractive candidates for visualization and imaging devices because of their high thermal/chemical stability and favorable luminescence characteristics. In the view that the phase structure, crystallinity, morphology (shape, size and dimensionality) and surface chemistry may significantly regulate the physical/chemical properties of a compound, extensive efforts have been devoted over the past decades to the design of multiform REPO4 and REVO4 crystallites via solution processing for luminescence manipulation. This review article highlights the recent achievements in this field, with an emphasis on solution chemistry, the role of chelate ions, the fundamental crystallization mechanism and the correlation of structure and luminescence properties. We hope that this review may provide insights into crystallite tailoring and luminescence optimization of inorganic compounds for lighting and display applications.